Bacteriological control of canned processed cheese - ΚΑΡΔΟΥΛΗΣ, Α.; ΣΚΟΥΝΤΖΟΣ, Κ.; ΓΙΑΝΝΟΥΣΗΣ, Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
The study describes the protocol of examining 210 lots of 9390 cans of processed canned cheese and discusses the findings.